KUALITAS PELAYANAN PRODUK HERBALIFE DI CLUB SYALALA GEMBIRA NUTRITION - Nur Oktavia, Elsya; Satriyo , R. S Budi (iLearning Journal Center, 2023)
This research proposes an in-depth analysis of the service quality of Herbalife products provided at Club Syalala Gembira Nutrition. Qualitative research methods were used, focusing on the experiences and perceptions of customers involved in the consumption of the products and services offered. Data collection was carried out through participant observation, in-depth interviews, and analysis of related documents. The results of the analysis highlight the need for improvement in several aspects of the service. Although customers generally expressed satisfaction with the quality of Herbalife products provided at Club Syalala Gembira Nutrition, some indicated a desire for improvement in terms of clarity of information regarding product benefits, recommended dosages and possible side effects. In addition, there is a demand for improvements in communication between staff and customers, as well as the provision of clearer and more accessible resources related to training and mentoring in product use. This research concludes that improvements in communication, information accessibility, and a stronger personal approach can significantly increase customer satisfaction and experience with Herbalife products at Club Syalala Gembira Nutrition Key word: Herbalife, Club Syalala Gembira Nutrition, Service Quality, Customer Experience, Communication